Saudi Garlic Outcome on Microbes Cause Gastrointestinal Infections. - Sherifa . Sabra (Basrah Journal of Veterinary Research)
Garlic (Allium sativum Linn.), commonly used possess a comprehensive range of antimicrobial action. The goal was to test the health properties of Saudi garlic to eliminate the gut pathogenic microbes. Methodology was included the collection of Saudi garlic, were prepared the extracts, and were tested the pathogenic microbes cause gastrointestinal infections. The results showed the first score was included Staphylococcus aureus was eliminated with the boil extract within twenty-four hours, and within forty-eight hours it was eliminated with the hot extract. The second score was included Shigella dysentery, Campylobacter jejuni, and Escherichia coli were eliminated within forty-eight hours by the hot and boil extract. The third score was included Closterdium sp., Bacillus cereus, and Salmonella enteritica were eliminated with the presence of some little colonies. The fourth score was included Candida sp., Aspergillus sp., Cryptococcus neoformans, and Saccharomyces services were partially eliminated. It was decided that the active substances in Saudi garlic were capable of eliminating pathogenic microbes cause gastrointestinal infections. It was suggested that the pharmacy department be active in determining the permissible quantity of Saudi garlic for an individual to use according to his health condition.